[PP.03.17] HYPERTENSION AND COGNITIVE FUNCTION IN THE ELDERLY: PRELIMINARY RESULTS OF A SCREENING STUDY. (September 2017) - Bulgaresi, M.; Menozzi, L.; Rivasi, G.; Sgrilli, F.; Giordano, A.; Latini, E.; Martella, L.; Mossello, E.; Ungar, A.; Marchionni, N.
Abstract : Objective: Hypertension is very common in older patients and is considered to be a risk factor for cognitive decline; the 2013 ESH/ESC Guidelines for the management of arterial hypertension suggest the use of cognitive evaluation tests in the clinical assessment of elderly hypertensive patients. Nonetheless, there is still controversy over which screening test is more appropriate and cognitive impairment is usually under-diagnosed in these patients. Our study evaluates the application of a first-line screening to assess cognitive function in old hypertensive patients without a previous diagnosis of cognitive impairment. Design and method: in this observational study we enrolled 80 consecutive hypertensive patients referred to our Centre for Hypertension in the Elderly and aged 65 years or older. All patients underwent a first-line cognitive evaluation with the Mini-Cog test, including three-item repetition and recall and clock drawing. If the Mini-Cog was suggestive for cognitive impairment, the patient was further evaluated with the Mini Mental State Examination (MMSE); in case of a MMSE score inferior to 28, a Neuropsychological Evaluation (NPE) was performed. Results: the mean age of our population was 75.7 ± 5.5 (range 66–90); the 27.5% was octogenarian. The mean number of drugs of patients' daily therapy was 6.5 ± 2.8, including 2.8 ± 1.2 anti-hypertensive drugs. For what concerns blood pressure (BP) control, all patients had both clinic and out-of-office BP values in the target range. Mean systolic and diastolic BP values were similar in patients with normal and abnormal Mini-Cog Test results. A Mini-Cog Test suggestive for cognitive impairment was observed in the 20% of our study population (16/80); 5 of these patients had a MMSE score inferior to 28. After the NPE, a diagnosis of cognitive decline was confirmed in 2 patients (2.5% of the population). The 39.1% of patients with a normal Mini-Cog Test performed an abnormal Clock Drawing Test (CDT), therefore the 51.3% of our study population had a deficit in clock drawing. Conclusions: According to our results, the Mini-Cog cannot be suggested as a screening test for the evaluation of cognitive function in old hypertensive patients.